Markers of lower respiratory tract infections in emergency departments - Tatar, Dursun; Senol, Gunes; Anar, Ceyda; Tibet, Gultekin (Multidisciplinary Respiratory Medicine, 2013)
Background: Acute respiratory tract infections are the common causes for admission to emergency department. Appropriate diagnosis and initiating treatment on time are important for reducing morbidity and mortality rate due to lower respiratory tract infection (LRTI). The aim of this study is to determine if C-reactive protein (CRP) levels and white blood cells (WBC) count are considerable markers to help rapid diagnosis and prediction of antibiotic need for lower respiratory infections in emergency departments. The relationships between infectious agents and those markers have also been evaluated. Methods: Study subjects and control group were selected by defined criteria. Patients were analyzed and assessed for CRP and WBC, sputum Gram stain and culture besides routine laboratory tests and chest X-Rays. Results: One hundred and ninety four episodes out of 175 patients were evaluated for the study. CRP level and WBC count were detected significantly higher in patients ofstudy group than in those of control group. Pseudomonas aeruginosa and Haemophilus influenzae were the pathogens most often isolated. Conclusion: In conclusion, CRP and WBC sputum are important markers for diagnosis of LRTI at the emergency departments and results of microbiological analysis of respiratory specimens were correlated with these markers. Trial registration: Registation number of ethic committee of Dr. Suat Seren Chest Diseases and Surgery Training and Research Hospital: 28.04.2006/114